MAYBE Initial complexity problem: 1: T: (1, 1) f3(a, b) -> f2(a, b) (?, 1) f2(a, b) -> f2(a - 1, b) [ 1 >= a ] (?, 1) f2(a, b) -> f300(a - 1, c) [ a >= 2 ] start location: f3 leaf cost: 0 Repeatedly removing leaves of the complexity graph in problem 1 produces the following problem: 2: T: (1, 1) f3(a, b) -> f2(a, b) (?, 1) f2(a, b) -> f2(a - 1, b) [ 1 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(a, b) with all transitions in problem 2, the following new transition is obtained: f3(a, b) -> f2(a - 1, b) [ 1 >= a ] We thus obtain the following problem: 3: T: (1, 2) f3(a, b) -> f2(a - 1, b) [ 1 >= a ] (?, 1) f2(a, b) -> f2(a - 1, b) [ 1 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(a - 1, b) [ 1 >= a ] with all transitions in problem 3, the following new transition is obtained: f3(a, b) -> f2(a - 2, b) [ 1 >= a /\ 1 >= a - 1 ] We thus obtain the following problem: 4: T: (1, 3) f3(a, b) -> f2(a - 2, b) [ 1 >= a /\ 1 >= a - 1 ] (?, 1) f2(a, b) -> f2(a - 1, b) [ 1 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(a - 2, b) [ 1 >= a /\ 1 >= a - 1 ] with all transitions in problem 4, the following new transition is obtained: f3(a, b) -> f2(a - 3, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 ] We thus obtain the following problem: 5: T: (1, 4) f3(a, b) -> f2(a - 3, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 ] (?, 1) f2(a, b) -> f2(a - 1, b) [ 1 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(a - 3, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 ] with all transitions in problem 5, the following new transition is obtained: f3(a, b) -> f2(a - 4, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 ] We thus obtain the following problem: 6: T: (1, 5) f3(a, b) -> f2(a - 4, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 ] (?, 1) f2(a, b) -> f2(a - 1, b) [ 1 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(a - 4, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 ] with all transitions in problem 6, the following new transition is obtained: f3(a, b) -> f2(a - 5, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 ] We thus obtain the following problem: 7: T: (1, 6) f3(a, b) -> f2(a - 5, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 ] (?, 1) f2(a, b) -> f2(a - 1, b) [ 1 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(a - 5, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 ] with all transitions in problem 7, the following new transition is obtained: f3(a, b) -> f2(a - 6, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 ] We thus obtain the following problem: 8: T: (1, 7) f3(a, b) -> f2(a - 6, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 ] (?, 1) f2(a, b) -> f2(a - 1, b) [ 1 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(a - 6, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 ] with all transitions in problem 8, the following new transition is obtained: f3(a, b) -> f2(a - 7, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 ] We thus obtain the following problem: 9: T: (1, 8) f3(a, b) -> f2(a - 7, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 ] (?, 1) f2(a, b) -> f2(a - 1, b) [ 1 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(a - 7, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 ] with all transitions in problem 9, the following new transition is obtained: f3(a, b) -> f2(a - 8, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 ] We thus obtain the following problem: 10: T: (1, 9) f3(a, b) -> f2(a - 8, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 ] (?, 1) f2(a, b) -> f2(a - 1, b) [ 1 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(a - 8, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 ] with all transitions in problem 10, the following new transition is obtained: f3(a, b) -> f2(a - 9, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 ] We thus obtain the following problem: 11: T: (1, 10) f3(a, b) -> f2(a - 9, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 ] (?, 1) f2(a, b) -> f2(a - 1, b) [ 1 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(a - 9, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 ] with all transitions in problem 11, the following new transition is obtained: f3(a, b) -> f2(a - 10, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 /\ 1 >= a - 9 ] We thus obtain the following problem: 12: T: (1, 11) f3(a, b) -> f2(a - 10, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 /\ 1 >= a - 9 ] (?, 1) f2(a, b) -> f2(a - 1, b) [ 1 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(a - 10, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 /\ 1 >= a - 9 ] with all transitions in problem 12, the following new transition is obtained: f3(a, b) -> f2(a - 11, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 /\ 1 >= a - 9 /\ 1 >= a - 10 ] We thus obtain the following problem: 13: T: (1, 12) f3(a, b) -> f2(a - 11, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 /\ 1 >= a - 9 /\ 1 >= a - 10 ] (?, 1) f2(a, b) -> f2(a - 1, b) [ 1 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(a - 11, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 /\ 1 >= a - 9 /\ 1 >= a - 10 ] with all transitions in problem 13, the following new transition is obtained: f3(a, b) -> f2(a - 12, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 /\ 1 >= a - 9 /\ 1 >= a - 10 /\ 1 >= a - 11 ] We thus obtain the following problem: 14: T: (1, 13) f3(a, b) -> f2(a - 12, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 /\ 1 >= a - 9 /\ 1 >= a - 10 /\ 1 >= a - 11 ] (?, 1) f2(a, b) -> f2(a - 1, b) [ 1 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(a - 12, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 /\ 1 >= a - 9 /\ 1 >= a - 10 /\ 1 >= a - 11 ] with all transitions in problem 14, the following new transition is obtained: f3(a, b) -> f2(a - 13, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 /\ 1 >= a - 9 /\ 1 >= a - 10 /\ 1 >= a - 11 /\ 1 >= a - 12 ] We thus obtain the following problem: 15: T: (1, 14) f3(a, b) -> f2(a - 13, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 /\ 1 >= a - 9 /\ 1 >= a - 10 /\ 1 >= a - 11 /\ 1 >= a - 12 ] (?, 1) f2(a, b) -> f2(a - 1, b) [ 1 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(a - 13, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 /\ 1 >= a - 9 /\ 1 >= a - 10 /\ 1 >= a - 11 /\ 1 >= a - 12 ] with all transitions in problem 15, the following new transition is obtained: f3(a, b) -> f2(a - 14, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 /\ 1 >= a - 9 /\ 1 >= a - 10 /\ 1 >= a - 11 /\ 1 >= a - 12 /\ 1 >= a - 13 ] We thus obtain the following problem: 16: T: (1, 15) f3(a, b) -> f2(a - 14, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 /\ 1 >= a - 9 /\ 1 >= a - 10 /\ 1 >= a - 11 /\ 1 >= a - 12 /\ 1 >= a - 13 ] (?, 1) f2(a, b) -> f2(a - 1, b) [ 1 >= a ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f2(a - 14, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 /\ 1 >= a - 9 /\ 1 >= a - 10 /\ 1 >= a - 11 /\ 1 >= a - 12 /\ 1 >= a - 13 ] with all transitions in problem 16, the following new transition is obtained: f3(a, b) -> f2(a - 15, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 /\ 1 >= a - 9 /\ 1 >= a - 10 /\ 1 >= a - 11 /\ 1 >= a - 12 /\ 1 >= a - 13 /\ 1 >= a - 14 ] We thus obtain the following problem: 17: T: (1, 16) f3(a, b) -> f2(a - 15, b) [ 1 >= a /\ 1 >= a - 1 /\ 1 >= a - 2 /\ 1 >= a - 3 /\ 1 >= a - 4 /\ 1 >= a - 5 /\ 1 >= a - 6 /\ 1 >= a - 7 /\ 1 >= a - 8 /\ 1 >= a - 9 /\ 1 >= a - 10 /\ 1 >= a - 11 /\ 1 >= a - 12 /\ 1 >= a - 13 /\ 1 >= a - 14 ] (?, 1) f2(a, b) -> f2(a - 1, b) [ 1 >= a ] start location: f3 leaf cost: 1 Complexity upper bound ? Time: 0.876 sec (SMT: 0.820 sec)